2023
DOI: 10.1186/s13047-023-00634-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supportive and minimalist footwear on standing balance and walking stability in older women

Abstract: Background Footwear has been shown to influence balance and is an important consideration in relation to the prevention of falls. However, it remains unclear as to what type of footwear is most beneficial for balance in older people: sturdy, supportive footwear, or minimalist footwear to maximise plantar sensory input. The objectives of this study were therefore to compare standing balance and walking stability in older women wearing these two footwear styles, and to investigate participants’ p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…Menz [26] and Nor Azhar [28] found little to no difference in most of the outcome measures when compared to minimalist shoes and participants own footwear. However, Menz [26] reported the balance-enhancing footwear significantly reduced step width and end sway compared to the minimalist footwear condition…”
Section: Balancing-enhancing Footwearmentioning
confidence: 98%
See 1 more Smart Citation
“…Menz [26] and Nor Azhar [28] found little to no difference in most of the outcome measures when compared to minimalist shoes and participants own footwear. However, Menz [26] reported the balance-enhancing footwear significantly reduced step width and end sway compared to the minimalist footwear condition…”
Section: Balancing-enhancing Footwearmentioning
confidence: 98%
“…Tabulated data of included study characteristics is shown in Table 1. Studies included in this review originated from 17 different countries: 13 (23.2%) studies originated from Australia [16][17][18][19][20][21][22][23][24][25][26][27][28], 10 (17.9%) from the USA [29][30][31][32][33][34][35][36][37][38], eight (14.3%) from China [39][40][41][42][43][44][45][46], five (9%) from Canada [47][48][49][50][51], three (5.4%) from Iran [52][53][54], two each from the UK [55,56] (3.6%), New Zealand [57,58] (3.6%), Germany [59,60] (3.6%) and Turkey [61,62] (3.6%), one each from J...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%